Talking (With) Trees: Arboreal Articulation and Poetics. Issue 3 (3rd July 2021) - Cooke, Stuart
ABSTRACT: Drawing on recent developments in critical plant studies, this essay attempts to develop an ethological poetics of trees. I start by analysing four examples of recent fiction, poetry and non-fiction that are each about different kinds of trees – The Overstory by Richard Powers; Translations from Bark Beetle by Jody Gladding; Tree Talks by Wendy Burk; The Biggest Estate on Earth by Bill Gammage – with relation to JC Ryan's phytocritical model. In addition to their representation of botanical lives, I also consider how Powers and Gammage understand trees as constitutive of Indigenous kinship networks. Then, I combine the insights gleaned from the textual analysis with work by Michael Marder and others in order to outline key features of tree ontology and articulation, and I conclude by positing a provisional arboreal poetics.